If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = 2y + -1 Reorder the terms: 4 + 3x = 2y + -1 Reorder the terms: 4 + 3x = -1 + 2y Solving 4 + 3x = -1 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = -1 + -4 + 2y Combine like terms: 4 + -4 = 0 0 + 3x = -1 + -4 + 2y 3x = -1 + -4 + 2y Combine like terms: -1 + -4 = -5 3x = -5 + 2y Divide each side by '3'. x = -1.666666667 + 0.6666666667y Simplifying x = -1.666666667 + 0.6666666667y
| 3x2/3-2= | | V^2/64 | | -21-4(2)-(-11)+(-18)=x | | .375x+.4x+180+270=x | | 5x+20=2x+10 | | y=2x^3-6x^2-56x | | f(6)=10-5x | | 4-4(3m-3)=-20 | | 3/4v=36 | | sin(3x+2)=0.5 | | 4.9t^2-17t+3.8=0 | | 12x-5+4x-11=8x | | t=4n+3 | | 0.95-0.35x=0.75x-10.05 | | 2(5(3(x-2)+4)+6(x-2))=0 | | .6n+.5=5.3 | | (6x-1)/(3x-2) | | x^2-2250x+31500=0 | | 4(-4)-3=13 | | D=14n+50 | | 10x^2+9-x=0 | | 5b+2x=3a | | 2h/9=-4 | | 4x+3*3x+4=574 | | 4y-3y+8(y-7)=0 | | 3y-11y=12y-8 | | 10=2u-14 | | x=3*ln(x) | | 3v/7-2=10 | | 6x+5=29+3x | | 5y+2y-6y=17-5-9 | | 5+6a+8a^2=0 |